Under Five Girls Found More Prone to Protein Energy Malnutrition Compared to Boys: A Squatter Settlement Study from Karachi - Nilofer Arshad; Fatima Jehangir; Amin Arshad; Tariq Adnan; Muzammil Murtaza (ziauddin University, 2024)
Background: Protein-energy malnutrition (PEM), is an imbalance between protein and energy intake and the body's requirement for optimal growth. In Pakistan, almost 40% of children, less than 5 years, have stunted growth, while 17.7% suffer from muscle wasting. This study aimed to explore the frequency of the different types of protein energy malnutrition in children under 5 years residing in Sikandarabad and evaluate the risk factors leading to this condition. Methods: This cross-sectional observational study, recruited 220 children less than 5 years of age. Previous health record was investigated. Physical examination was done and anthropometric measurements of each child were plotted on WHO/CDC Growth Standard Charts to classify the degree of protein energy malnutrition. Binary and multivariate logistic regression was computed to see a significant association with the outcome. Results: The prevalence of PEM was 136(61.5%). Overall girls were underweight (9±3.8 kg) and stunted (77.2±16.1) compared to boys. Delayed weaning was a significant risk factor for PEM (p=0.044). The majority of children belonged to Low socio-economic status 65(47.8%), with more than 2 siblings. However, 40(29.4%) of those below 5 years were malnourished. A positive association (OR:1.37,1.21) was found between PEM and acute illnesses (56.6%), worm infestation (14%) and measles outbreaks (5.9%). Conclusion: Young girls (9±3.8 kg) were found severely undernourished compared to boys. This is probably because of bias attitude toward gender preference in the distribution of quality food (p=0.14). Keywords: Protein Energy Malnutrition; Underweight; Stunting; Wasting; Overweight.